2010
DOI: 10.4041/kjod.2010.40.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurements of tooth mobility following orthodontic treatment

Abstract: Objective:The aim of the present study was to evaluate the changes in tooth mobility following orthodontic treatment and to obtain information regarding the guideline of retainer wear duration during the post-treatment period. Methods: The sample consisted of twenty patients who had been treated with edgewise appliances. The mobility of the maxillary teeth from the central incisor to the first molar was measured bilaterally by way of the Periotest Ⓡ , a non-invasive, electronic device that provides an objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the current study, tooth mobility decreased immediately after the LR was applied, and there was no signi cant difference in mobility among all the study groups 10 months later. The difference in the ndings may be due to the fact that Hwang et al [10] measured the mobility of the upper teeth and that no LR was applied.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the current study, tooth mobility decreased immediately after the LR was applied, and there was no signi cant difference in mobility among all the study groups 10 months later. The difference in the ndings may be due to the fact that Hwang et al [10] measured the mobility of the upper teeth and that no LR was applied.…”
Section: Discussionmentioning
confidence: 95%
“…Hwang et al [10] evaluated changes in tooth mobility at quarterly intervals for two years after orthodontic treatment using a Periotest® device and found that tooth mobility decreased rapidly in the rst six months and at a slower rate in the following six months. In the current study, tooth mobility decreased immediately after the LR was applied, and there was no signi cant difference in mobility among all the study groups 10 months later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 5 relevant studies based on their subject and publication date were chosen to be discussed in detail (Table 1). As shown, it is rational to consider a strong relationship between physiological or systemic conditions and generalized tooth mobility [6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%